2004
DOI: 10.1111/j.1348-0421.2004.tb03624.x
|View full text |Cite
|
Sign up to set email alerts
|

The Larval Specific Lymphatic Filarial ALT‐2: Induction of Protection Using Protein or DNA Vaccination

Abstract: Genes from the infective stage of lymphatic filarial parasites expressed at the time of host invasion have been identified as potential vaccine candidates. By screening an L3 cDNA library with sera from uninfected longstanding residents of an area endemic for onchocerciasis, so‐called “endemic normals” (EN), we have cloned and characterized one such gene termed the abundant larval transcript two (ALT‐2). The stage specificity of ALT‐2 gene transcription and protein synthesis was confirmed by PCR using gene‐spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 43 publications
(34 reference statements)
1
53
1
Order By: Relevance
“…The pathologic progression of this disease is intriguing and gruesome making it a difficult task to develop a vaccine against this multicellular parasite. Of the different vaccine candidates identified for lymphatic filariasis, the ALT-2 protein stands out as a remarkable one with no known homologue in mammalian hosts, imparting about 74% protection in jirds [13][14][15][16][17][18][19][20][21][22]. This study will lead to the development of commercial largescale production of BmALT-2 as an inexpensive vaccine candidate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathologic progression of this disease is intriguing and gruesome making it a difficult task to develop a vaccine against this multicellular parasite. Of the different vaccine candidates identified for lymphatic filariasis, the ALT-2 protein stands out as a remarkable one with no known homologue in mammalian hosts, imparting about 74% protection in jirds [13][14][15][16][17][18][19][20][21][22]. This study will lead to the development of commercial largescale production of BmALT-2 as an inexpensive vaccine candidate.…”
Section: Resultsmentioning
confidence: 99%
“…Bmalt-2 of B. malayi (accession number U84723) was a kind gift from Dr Thomas B. Nutman, National Institutes of Health, Bethesda, MD, USA. Bmalt-2 was cloned in pRSETB vector as described by Ramachandran et al [21]. Bmalt-2 was amplified from pRSETB/Bmalt-2 plasmid construct by polymerase chain reaction (PCR) (Applied Biosystems, Foster City, CA, USA) with PR DNA polymerase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that Ramachandran et al (13) have found that normal individuals in an area of endemicity react to purified BmALT-2 more strongly than individuals with asymptomatic microfilaremia. One is tempted to speculate that the reason that individuals with asymptomatic microfilaremia harbor high worm burdens may be because of their inability to produce high-level antibody responses to this candidate antigen.…”
Section: Discussionmentioning
confidence: 99%
“…For example, abundant larval transcript (ALT) gene (Gregory et al 2000;Gnanasekar et al 2004;Ramachandran et al 2004), which, as the name suggest is abundantly expressed in L3 stages of the parasite, has been shown to provide significant levels of protection in animal models. Although the nature of protective immune responses is highly debated over several years (Peralta et al 1999;Ravindran et al 2000), the consensus is that the host immune responses play a major role in determining clinical manifestations of various groups (Frank and Grieve 1996;Helmy et al 2000).…”
Section: Introductionmentioning
confidence: 99%